How Research Drives Climate, Peace and Humanitarian Outcomes: Lessons learned from harvesting, producing, and reflecting on outcome stories from CGIAR Climate Security research at the Alliance of Bioversity International and CIAT - Gadeberg, Marianne; Pacillo, Grazia; Läderach, Peter R.D. (2025)
CGIAR's Climate Security team developed a methodology for documenting research outcomes through story formats, serving as a strategic tool for reflection and learning. The team achieved 12 outcomes in 2023-2024, from informing Kenya's National Climate Change Action Plan to enabling UNHCR's call to protect 90 million climate-vulnerable people.